2018
DOI: 10.4236/ijcm.2018.99060
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster in Diverse Situations: A Review

Abstract: Herpes zoster occurred when the suppressive ability of immune system failed to prevent the reactivation of initial varicella-zoster virus infection. Its frequency is higher among immune compromised individuals. Herpes zoster presents with characteristic painful grouped vesicles on erythematous background along the dermatome area and could be complicated by post-herpetic neuralgia. The current review examined the risk factors and discussed herpes zoster in different situations, treatment and concluded by discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 83 publications
1
3
0
1
Order By: Relevance
“…The rapid response of the patient to biopentin without antiviral medication may have confirmed our impression. Other studies in agreement with this current report, have shown that tricyclic antidepressants and gabapentin either as a single agent or in combination are effective in treating post-ww.njdres.com herpetic neuralgia by reducing the severity and duration of the pain 9,10 The diagnostic dilemma of this case was not only a result of the peculiarities stated above but also the rarity of the involvement of the mandibular branch of the trigeminal nerve in herpes zoster infection as confirmed by the lack of publication of case reports on herpes zoster mandibularis from Nigeria. The negative impact of this condition on the quality of life and the susceptibility of the patient to substance/drug abuse is enough reason to advocate a routine vaccination scheme against VZV in Africa like in other developed nations 14 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The rapid response of the patient to biopentin without antiviral medication may have confirmed our impression. Other studies in agreement with this current report, have shown that tricyclic antidepressants and gabapentin either as a single agent or in combination are effective in treating post-ww.njdres.com herpetic neuralgia by reducing the severity and duration of the pain 9,10 The diagnostic dilemma of this case was not only a result of the peculiarities stated above but also the rarity of the involvement of the mandibular branch of the trigeminal nerve in herpes zoster infection as confirmed by the lack of publication of case reports on herpes zoster mandibularis from Nigeria. The negative impact of this condition on the quality of life and the susceptibility of the patient to substance/drug abuse is enough reason to advocate a routine vaccination scheme against VZV in Africa like in other developed nations 14 .…”
Section: Discussionsupporting
confidence: 90%
“…There is general paucity of data on Herpes zoster affecting the mandibular nerve. Authors are not aware of any clinical case report on herpes zoster mandibularis from Africa in the English literature 10,11 . Reactivation of the VZV, in this case, maybe due to advancing age and impaired immunity due to Diabetes Mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Setelah terjadi varicella, sistem imun tubuh dapat membunuh varicella Zoster namun kadangkala supresi oleh sistem imun gagal untuk mencegahnya. Ketika reaktivasi virus terjadi, virus ini diangkut ke mikrotubulus dalam akson sensoris dan menginfeksi sel epitel, yang berujung ke pembentukan ruam yang bermanifestasi rasa nyeri dan gatal serta berlokasi di daerah dermatom yang terkena secara unilateral (Olabode, 2018).…”
Section: Aspek Klinikunclassified
“…This includes elderly people, patients with lymphoma, HIV or those receiving chemotherapy or steroids. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%